1997
DOI: 10.1073/pnas.94.12.6474
|View full text |Cite
|
Sign up to set email alerts
|

Orally absorbed reactive glycation products (glycotoxins): An environmental risk factor in diabetic nephropathy

Abstract: Endogenous advanced glycation endproducts (AGEs) include chemically crosslinking species (glycotoxins) that contribute to the vascular and renal complications of diabetes mellitus (DM). Renal excretion of the catabolic products of endogenous AGEs is impaired in patients with diabetic or nondiabetic kidney disease (KD). The aim of this study was to examine the oral absorption and renal clearance kinetics of food AGEs in DM with KD and whether circulating diet-derived AGEs contain active glycotoxins. Thirty-eigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
636
0
38

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 737 publications
(697 citation statements)
references
References 24 publications
(39 reference statements)
13
636
0
38
Order By: Relevance
“…However, this is the first time that an increase in all three AGE subtypes has been demonstrated in ZDF rats, an increase that was suppressed simultaneously by drug intervention. In patients with diabetic nephropathy, urinary excretion of CML is reduced, and insufficient clearance may result in increased serum AGE concentrations as well as tissue accumulation of AGEs [26][27][28][29]. This is further supported by the fact that the AGE inhibitor aminoguanidine improved renal function in diabetic nephropathy, reduced tissue AGE deposits [30][31][32] and increased urinary excretion of dietary AGEs [33].…”
Section: Discussionmentioning
confidence: 91%
“…However, this is the first time that an increase in all three AGE subtypes has been demonstrated in ZDF rats, an increase that was suppressed simultaneously by drug intervention. In patients with diabetic nephropathy, urinary excretion of CML is reduced, and insufficient clearance may result in increased serum AGE concentrations as well as tissue accumulation of AGEs [26][27][28][29]. This is further supported by the fact that the AGE inhibitor aminoguanidine improved renal function in diabetic nephropathy, reduced tissue AGE deposits [30][31][32] and increased urinary excretion of dietary AGEs [33].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the metabolic consequences of diabetes may have a higher impact on AGE accumulation than oxidative stress induced by smoking. Tissue AGE accumulation may be further influenced by nutrition [34].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products AGEs are long known to form in foods during heating (Lee et al ., 1981; O'Brien & Morrissey, 1989; Koschinsky et al ., 1997). There are two well‐characterized compounds, N ‐carboxy methyl‐lysine (CML) and methyl‐glyoxal (MG), derivatives of glucose–protein or glucose–lipid interactions, which serve as markers for AGEs (Dyer et al ., 1992; Vlassara & Palace, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…There are two well‐characterized compounds, N ‐carboxy methyl‐lysine (CML) and methyl‐glyoxal (MG), derivatives of glucose–protein or glucose–lipid interactions, which serve as markers for AGEs (Dyer et al ., 1992; Vlassara & Palace, 2002). A positive correlation is shown between the amount of AGEs consumed and that found in the circulation (Koschinsky et al ., 1997; He et al ., 1999). Consistent with our findings of high serum MG association with faster cognitive decline, we have shown that in the elderly, consumption of high dietary AGEs is associated with a faster rate of cognitive decline (Cai et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%